Physiotherapy in obstructive airways disease - D. Gaskell (AOSIS, 1978)
The physiotherapy technique used in the treatment of asthma, chronic bronchitis and emphysema are very similar, but their application in the treatment of these diseases is totally different. For this reason the diseases will be dealt with separately.